MPVE double-wall corrugated pipe with high rolling resistance and preparation method thereof

MPVE double-wall corrugated pipe prepared through multi-layer modification process solves the problem of insufficient performance of traditional pipes in complex use scenarios, and achieves the improvement of high crush resistance, corrosion resistance and mechanical performance, meeting the needs of high standards of engineering.

CN119502468AInactive Publication Date: 2025-02-25BAODING BOSIRI PLASTIC MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411790778.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional double-wall corrugated pipes show insufficient mechanical properties, poor corrosion resistance and poor manufacturing process in complex use scenarios, which are difficult to meet the needs of high-standard engineering.

Method used

A multi-layer modification process is used to prepare high-crunching resistance MPVE double-wall corrugated pipe. Through the multi-layer structural design of the inner layer, the intermediate reinforcement layer and the outer layer, combined with multiple modification reactions of the modified resin and the anticorrosion coating, a high-performance resin structure is constructed.

Benefits of technology

It significantly improves the high crush resistance, corrosion resistance and physical and mechanical properties of the pipe, meets the use requirements in complex environments, extends the service cycle of the pipe and reduces operation and maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005175263510000181
    Figure BDA0005175263510000181
  • Figure BDA0005175263510000191
    Figure BDA0005175263510000191
Patent Text Reader

Abstract

The invention discloses a high-rolling-resistance MPVE double-wall corrugated pipe and a preparation method thereof, and relates to the technical field of plastic pipes, the high-rolling-resistance MPVE double-wall corrugated pipe comprises an inner layer, a middle reinforcing layer and an outer layer; the inner layer is specifically prepared from the following components in parts by mass: 60 to 70 parts of MPVE alloy, 8 to 12 parts of dioctyl phthalate, 2 to 4 parts of calcium-zinc composite stabilizer, 0.5 to 1.5 parts of antioxidant, 1 to 3 parts of polyethylene wax and 1 to 3 parts of calcium stearate and zinc stearate composite lubricant. According to the high-rolling-resistance MPVE double-wall corrugated pipe and the preparation method thereof, modified resin is synthesized through a multi-step modification process and four modification reactions, a high-performance resin structure is gradually constructed from introduction of active groups to a copolymerization reaction to introduction of functional monomers and a crosslinking reaction, the performance of the resin can be accurately controlled, and the service life of the corrugated pipe is prolonged. And the use requirement of the corrugated pipe in a complex environment is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic pipes, and in particular to a high-rolling-resistant MPVE double-wall corrugated pipe and a preparation method thereof. Background Art

[0002] In many fields such as modern engineering construction, municipal drainage, and underground pipe network laying, plastic pipes are widely used due to their light weight, corrosion resistance, and easy installation. Double-wall corrugated pipes stand out with their unique structural advantages. Traditional double-wall corrugated pipes are usually made of materials such as polyethylene (PE) and polyvinyl chloride (PVC). However, as the use scenarios become increasingly complex and demanding, conventional pipes have exposed many performance shortcomings and are difficult to meet actual needs.

[0003] In the process of pipe processing and manufacturing, the traditional technology has insufficient control over the composite synergy of each layer of materials, the bonding force between the layers is weak, and it is easy to delaminate and debond when subjected to force, affecting the overall mechanical properties of the pipe. In addition, the conventional formula system is single, and it is difficult to take into account the multiple requirements of flexibility, rigidity and durability, which limits the improvement of the comprehensive performance of the product and hinders the promotion and application of pipes in high-standard engineering scenarios.

[0004] There is an urgent need to develop a double-wall corrugated pipe with excellent high rolling resistance, strong corrosion resistance and excellent manufacturing process to meet the complex and changeable working conditions, extend the service life of the pipeline, reduce operation and maintenance costs, and ensure project quality and environmental safety. The MPVE double-wall corrugated pipe with high rolling resistance of the present invention came into being, which specifically overcomes the above technical difficulties. Summary of the invention

[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: a high rolling resistance MPVE double-wall corrugated pipe, comprising an inner layer, an intermediate reinforcement layer and an outer layer;

[0006] Wherein, the inner layer is specifically composed of the following components:

[0007] 60-70 parts by mass of MPVE alloy, 8-12 parts by mass of dioctyl phthalate, 2-4 parts by mass of calcium-zinc composite stabilizer, 0.5-1.5 parts by mass of antioxidant, 1-3 parts by mass of polyethylene wax, and 1-3 parts by mass of calcium stearate and zinc stearate composite lubricant;

[0008] The intermediate reinforcement layer is specifically composed of the following components:

[0009] 15-20 parts by mass of glass fiber, 10-15 parts by mass of glass microbeads, 50-60 parts by mass of MPVE alloy, 0.5-2 parts by mass of carbon nanotubes, 2-4 parts by mass of silane coupling agent, 6-10 parts by mass of dioctyl phthalate, 2-4 parts by mass of calcium zinc composite stabilizer, 0.5-1.5 parts by mass of calcium stearate and 0.5-1.5 parts by mass of antioxidant;

[0010] The outer layer is specifically composed of the following components:

[0011] 10-15 parts by mass of modified resin, 40-50 parts by mass of MPVE alloy, 0.5-1.5 parts by mass of phosphite antioxidant, 2-4 parts by mass of benzotriazole ultraviolet absorber, 3-5 parts by mass of masterbatch, 10-15 parts by mass of ceramic micropowder filler, 1-3 parts by mass of nano titanium dioxide filler, 5-8 parts by mass of plasticizer, 1-3 parts by mass of stabilizer, 0.5-1.5 parts by mass of corrosion inhibitor and 3-7 parts by mass of anti-corrosion coating.

[0012] Preferably, the preparation method of the modified resin is specifically as follows:

[0013] Step A1, first modification, maleic anhydride grafting:

[0014] Preheating ethylene-vinyl acetate copolymer to 80-100° C. in a high-speed mixer, then adding maleic anhydride and initiator dicumyl peroxide, mixing thoroughly, and reacting and extruding the mixture in a twin-screw extruder to obtain a first modified product A;

[0015] The vinyl acetate content of the ethylene-vinyl acetate copolymer is 18%-28%, the melt index is between 2-5g / 10min, the maleic anhydride accounts for 2%-3% of the mass of the ethylene-vinyl acetate copolymer, and the initiator dicumyl peroxide accounts for 0.5%-1% of the mass of the ethylene-vinyl acetate copolymer;

[0016] Step A2, second modification, copolymerization with acrylic ester monomers:

[0017] The first modified product A obtained is placed in a reactor, the reactor is heated to 70-80° C., an initiator and 30%-50% of an emulsifier are added, and then butyl acrylate, methyl methacrylate and the remaining emulsifier are slowly added dropwise to obtain a second modified product B;

[0018] The mass ratio of butyl acrylate to methyl methacrylate and the first modified product A is 3:2:5, the emulsifier is sodium dodecyl sulfate, and the amount is 2%-3% of the weight of butyl acrylate and methyl methacrylate, and the initiator is potassium persulfate, and the amount is 0.5%-1% of the weight of butyl acrylate and methyl methacrylate;

[0019] Step A3, the third modification, introduction of fluorinated monomers:

[0020] In a reaction kettle equipped with a stirrer and a condenser, using toluene as a solvent, the second modified product B, perfluoroalkyl ethyl acrylate, emulsifier octylphenol polyoxyethylene ether and azobisisobutyronitrile are mixed, the reaction system is heated to 60-70° C., and reacted for 4-6 hours under nitrogen protection to obtain the third modified product C;

[0021] The mass ratio of the perfluoroalkyl ethyl acrylate to the second modified product B is 1:4, and the amount of the emulsifier octylphenol polyoxyethylene ether is 1%-2% of the total mass of the second modified product B;

[0022] Step A4, fourth modification, cross-linking reaction:

[0023] The third modified product C is mixed with trimethylolpropane triacrylate and 1-hydroxy-cyclohexyl-phenyl-ketone, and cross-linked under ultraviolet light. The wavelength of ultraviolet light is 365nm, and the intensity of irradiation is 50-100mW / cm 2 , the irradiation time is 10-20 minutes to obtain a modified resin, and the final product modified resin is obtained;

[0024] The amount of trimethylolpropane triacrylate used is 2%-3% of the mass of the third modified product C, and the amount of 1-hydroxy-cyclohexyl-phenyl-ketone used is 1%-2% of the mass of trimethylolpropane triacrylate.

[0025] Preferably, the preparation steps of the anti-corrosion coating are specifically as follows:

[0026] Step S1, polyurethane prepolymer synthesis:

[0027] In a reactor equipped with a stirrer, a thermometer and a nitrogen protection device, add polyether polyol and a catalyst into the reactor, heat it to 60-70°C, and stir evenly;

[0028] Slowly add diisocyanate dropwise to obtain a polyurethane prepolymer solution; a nitrogen atmosphere must be maintained during the reaction to prevent impurities such as moisture from interfering with the reaction.

[0029] Wherein, the diisocyanate is specifically toluene diisocyanate, and the amount of the diisocyanate is 80-100 parts by mass, which provides isocyanate groups for subsequent reactions; the polyether polyol is specifically polyoxypropylene glycol, and the amount of the polyoxypropylene glycol is 100-120 parts by mass, which serves as a soft segment to impart flexibility to the coating; the catalyst is specifically stannous octoate, and the amount thereof is 0.1-0.3 parts by mass, which is used to accelerate the reaction; the solvent is specifically ethyl acetate, which is used to adjust the viscosity of the system to facilitate the reaction;

[0030] Step S2, synthesis of silane coupling agent modified polyurethane prepolymer:

[0031] The polyurethane prepolymer solution obtained by the first reaction is cooled to 40-50°C, dibutyltin dilaurate is added, stirred evenly, and then γ-glycidyloxypropyltrimethoxysilane is slowly added dropwise. After the addition is completed, the mixture is reacted at 50-60°C for 3-4 hours;

[0032] The amount of γ-glycidyloxypropyltrimethoxysilane is 10-15 parts by mass, the silane coupling agent is used to enhance the adhesion between the coating and the outer wall of the pipe and introduce reactive groups, and the specific amount of dibutyltin dilaurate is 0.5-1 parts by mass, which serves as a catalyst for the reaction between the silane coupling agent and the polyurethane prepolymer;

[0033] The isocyanate groups in the polyurethane prepolymer react with the epoxy groups in KH-560, while the methoxy groups in the silane part can be involved in the subsequent hydrolysis reaction;

[0034] Step S3, introducing fluorinated acrylate monomer:

[0035] In a reactor, mix the product after the second reaction with an emulsifier and half of the initiator, and heat to 70-80°C;

[0036] Slowly adding a mixture of perfluorooctyl ethyl acrylate and the remaining initiator dropwise, and obtaining a fluorinated acrylate-modified polyurethane solution after the reaction is completed;

[0037] The fluorinated acrylate monomer undergoes polymerization reaction with the active groups (such as the remaining isocyanate groups or epoxy groups, etc.) on the polyurethane prepolymer under the action of the initiator;

[0038] The specific amount of perfluorooctyl ethyl acrylate is 10-15 parts by mass, the fluorine-containing monomer is used to improve the corrosion resistance and low surface energy characteristics of the coating, the initiator is specifically azobisisobutyronitrile, the amount of which is 0.5-1 parts by mass, used to initiate the polymerization reaction, and the emulsifier is specifically sodium dodecyl sulfate, the amount of which is 1-2 parts by mass, which helps to disperse the monomer in the system;

[0039] Step S4, cross-linking reaction and toughening modification:

[0040] The product after the third reaction is mixed evenly with trimethylolpropane triacrylate, carboxyl nitrile rubber and 1-hydroxy-cyclohexyl-phenyl-ketone, and cross-linked under ultraviolet light to finally obtain an anti-corrosion coating.

[0041] Trimethylolpropane triacrylate undergoes a cross-linking reaction with the unsaturated acrylate groups in the coating under the action of a photoinitiator. The active groups in the carboxyl nitrile rubber can further react with the isocyanate groups in the polyurethane to enhance interfacial bonding and improve toughness.

[0042] The modified anti-corrosion coating obtained after the above four reactions not only has good corrosion resistance, but also has excellent anti-cracking performance through the introduction of polyurethane soft segments, toughening agents, etc., and can better protect the outer wall of the corrugated pipe.

[0043] Preferably, in step S1, the reaction temperature is controlled not to exceed 80° C. when the diisocyanate is added dropwise, and the reaction is continued at 70-80° C. for 2-3 hours after the addition is completed.

[0044] Preferably, in step S3, the dropping time is controlled at 2-3 hours, and the reaction temperature is maintained at 75-85°C.

[0045] Preferably, the wavelength of the ultraviolet light in step S4 is 365 nm, and the irradiation intensity is 50-100 mW / cm 2 The irradiation time is 10-20 minutes.

[0046] A method for preparing a MPVE double-wall corrugated pipe with high rolling resistance, characterized in that it comprises the following steps:

[0047] Step D1, according to the inner layer formula, accurately weigh the MPVE alloy, dioctyl phthalate, calcium zinc composite stabilizer, antioxidant, polyethylene wax and calcium stearate and zinc stearate composite lubricant, and place them in containers for standby use;

[0048] The weighed MPVE alloy is put into a high-speed mixer, and dioctyl phthalate, calcium zinc composite stabilizer, antioxidant, polyethylene wax, and calcium stearate and zinc stearate composite lubricant are added in sequence during stirring. The stirring is continued during the feeding process, and the mixing time is controlled within 10-15 minutes to obtain a preliminarily mixed and uniform inner layer material;

[0049] The inner layer material after high-speed mixing is transported to the twin-screw extruder, and the die head extrude to form the inner layer tube blank;

[0050] Step D2, drying the glass fibers and glass microbeads, weighing the carbon nanotubes and the silane coupling agent, and stirring to obtain modified carbon nanotubes;

[0051] Weighing the treated glass fibers, glass microbeads, modified carbon nanotubes, MPVE alloy, dioctyl phthalate, calcium zinc composite stabilizer, calcium stearate and antioxidant, putting them into a high-speed mixer, and extruding them through an extruder to obtain a middle layer material;

[0052] Step D3, accurately weighing materials according to the outer layer formula, pre-dispersing the ceramic micropowder filler and the nano titanium dioxide filler, adding the weighed raw materials into a mixer, first adding the MPVE alloy and the modified resin and starting stirring, then adding the phosphite antioxidant, the benzotriazole ultraviolet absorber, the masterbatch, the dispersed ceramic micropowder filler, the nano titanium dioxide filler, the plasticizer, the stabilizer, the corrosion inhibitor and the anti-corrosion coating, mixing and extruding through an extruder to obtain the outer layer material;

[0053] Step D4: using a mold, the inner layer tube blank, the middle layer material, and the outer layer material are extruded simultaneously, and the extruded three-layer integrated tube blank is placed in a vacuum setting machine to finally produce a double-wall corrugated pipe finished product.

[0054] Preferably, in step D2, the carbon nanotubes and the silane coupling agent are weighed and put into a stirrer and stirred for 30-60 minutes.

[0055] Preferably, the die used is a co-extrusion die, and the overall extrusion speed is 1-2 m / min.

[0056] Preferably, the vacuum degree of the vacuum setting machine in step D4 is -0.08 to -0.1 MPa, and cooling is performed by a circulating water cooling system, and the cooling water temperature is controlled at 15-25°C.

[0057] The present invention provides a high rolling resistance MPVE double-wall corrugated pipe and a preparation method thereof.

[0058] Beneficial effects:

[0059] 1. The MPVE double-wall corrugated pipe with high rolling resistance and its preparation method, through a multi-step modification process, four modification reactions to synthesize the modified resin, from the introduction of active groups to copolymerization, to the introduction of functional monomers and cross-linking reactions, gradually construct a resin structure with high performance, which can accurately control the performance of the resin and meet the use requirements of the corrugated pipe in complex environments.

[0060] 2. The MPVE double-wall corrugated pipe with high rolling resistance and its preparation method, by integrating multiple functional groups such as maleic anhydride, acrylate, fluorine-containing monomers into the modified resin, make the resin have good flexibility, corrosion resistance, weather resistance, hardness and strength, thereby improving the performance of the corrugated pipe.

[0061] 3. The MPVE double-wall corrugated pipe with high rolling resistance and its preparation method, through the anti-corrosion coating undergoing multiple modification reactions, combines multiple technologies such as silane coupling agent modification, epoxy group introduction, fluorinated acrylate monomer polymerization, cross-linking and toughening. This multi-level modification method not only improves the adhesion between the coating and the pipe, but also enhances the coating's own anti-corrosion, anti-cracking and weathering properties, forming a coating system with comprehensive protection capabilities.

[0062] 4. The MPVE double-wall corrugated pipe with high rolling resistance and its preparation method are modified multiple times through modified resin, and various corrosion-resistant functional groups such as fluorine-containing groups are introduced into its molecular structure, which can effectively resist the erosion of various chemical substances such as acids, alkalis, salts, organic solvents, etc.

[0063] 5. The MPVE double-wall corrugated pipe with high rolling resistance and its preparation method have UV absorbers and antioxidants added to the anti-corrosion coating, and the structure of the modified resin itself also has anti-aging properties; it can maintain good performance whether it is exposed to ultraviolet radiation, temperature changes, humidity changes outdoors for a long time, or in complex environments such as the presence of chemical gases indoors. DETAILED DESCRIPTION

[0064] The present invention will be further described in detail below in conjunction with specific embodiments. The embodiments of the present invention are provided for the purpose of illustration and description, and are not intended to be exhaustive or to limit the present invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described to better illustrate the principles and practical applications of the present invention, and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

[0065] In the first embodiment, the present invention provides a technical solution:

[0066] A method for preparing a MPVE double-wall corrugated pipe with high rolling resistance comprises the following steps:

[0067] Step D1, according to the inner layer formula, accurately weigh the MPVE alloy, dioctyl phthalate, calcium zinc composite stabilizer, antioxidant, polyethylene wax and calcium stearate and zinc stearate composite lubricant, and place them in containers for standby use;

[0068] The weighed MPVE alloy is put into a high-speed mixer, and dioctyl phthalate, calcium zinc composite stabilizer, antioxidant, polyethylene wax, and calcium stearate and zinc stearate composite lubricant are added in sequence during stirring. The stirring is continued during the feeding process, and the mixing time is controlled within 10 minutes to obtain a preliminarily mixed and uniform inner layer material;

[0069] The inner layer material after high-speed mixing is transported to the twin-screw extruder, and the die head extrude to form the inner layer tube blank;

[0070] Step D2, drying the glass fibers and glass beads, weighing the carbon nanotubes and the silane coupling agent, stirring them, and putting them into a stirrer for 50 minutes to obtain modified carbon nanotubes;

[0071] Weighing the treated glass fibers, glass microbeads, modified carbon nanotubes, MPVE alloy, dioctyl phthalate, calcium zinc composite stabilizer, calcium stearate and antioxidant, putting them into a high-speed mixer, and extruding them through an extruder to obtain a middle layer material;

[0072] Step D3, accurately weighing materials according to the outer layer formula, pre-dispersing the ceramic micropowder filler and the nano titanium dioxide filler, adding the weighed raw materials into a mixer, first adding the MPVE alloy and the modified resin and starting stirring, then adding the phosphite antioxidant, the benzotriazole ultraviolet absorber, the masterbatch, the dispersed ceramic micropowder filler, the nano titanium dioxide filler, the plasticizer, the stabilizer, the corrosion inhibitor and the anti-corrosion coating, mixing and extruding through an extruder to obtain the outer layer material;

[0073] Step D4: using a co-extrusion die at an extrusion speed of 1.5 m / min, the inner layer tube blank, the middle layer material, and the outer layer material are extruded simultaneously, and the extruded three-layer integrated tube blank is placed in a vacuum setting machine with a vacuum degree of -0.08 to -0.1 MPa. At the same time, it is cooled by a circulating water cooling system, and the cooling water temperature is controlled at 20°C to finally produce a double-wall corrugated pipe product.

[0074] The second embodiment is based on the first embodiment:

[0075] A high rolling resistance MPVE double-wall corrugated pipe, comprising an inner layer, an intermediate reinforcement layer and an outer layer;

[0076] Wherein, the inner layer is specifically composed of the following components:

[0077] 60 parts by mass of MPVE alloy, 8 parts by mass of dioctyl phthalate, 2 parts by mass of calcium-zinc composite stabilizer, 0.5 parts by mass of antioxidant, 1 part by mass of polyethylene wax, and 1 part by mass of calcium stearate and zinc stearate composite lubricant;

[0078] The intermediate reinforcement layer is specifically composed of the following components:

[0079] 15 parts by mass of glass fiber, 10 parts by mass of glass microbeads, 50 parts by mass of MPVE alloy, 0.5 parts by mass of carbon nanotubes, 2 parts by mass of silane coupling agent, 6 parts by mass of dioctyl phthalate, 2 parts by mass of calcium zinc composite stabilizer, 0.5 parts by mass of calcium stearate and 0.5 parts by mass of antioxidant;

[0080] The outer layer is specifically composed of the following components:

[0081] 10 parts by mass of modified resin, 40 parts by mass of MPVE alloy, 0.5 parts by mass of phosphite antioxidant, 2 parts by mass of benzotriazole ultraviolet absorber, 3 parts by mass of masterbatch, 10 parts by mass of ceramic micropowder filler, 1 part by mass of nano titanium dioxide filler, 5 parts by mass of plasticizer, 1 part by mass of stabilizer, 0.5 parts by mass of corrosion inhibitor, and 3 parts by mass of anti-corrosion coating.

[0082] The preparation method of the modified resin is specifically as follows:

[0083] Step A1, first modification, maleic anhydride grafting:

[0084] Preheating ethylene-vinyl acetate copolymer to 80° C. in a high-speed mixer, then adding maleic anhydride and initiator dicumyl peroxide, and mixing thoroughly, and extruding the mixture in a twin-screw extruder to obtain a first modified product A;

[0085] The vinyl acetate content in the ethylene-vinyl acetate copolymer is 18%, the melt index is between 2g / 10min, the maleic anhydride accounts for 2% of the mass of the ethylene-vinyl acetate copolymer, and the initiator dicumyl peroxide accounts for 0.5% of the mass of the ethylene-vinyl acetate copolymer;

[0086] Step A2, second modification, copolymerization with acrylic ester monomers:

[0087] The first modified product A obtained was placed in a reactor, the reactor was heated to 70° C., an initiator and 30% of an emulsifier were added, and then butyl acrylate, methyl methacrylate and the remaining emulsifier were slowly added dropwise to obtain a second modified product B;

[0088] The mass ratio of butyl acrylate to methyl methacrylate and the first modified product A is 3:2:5, the emulsifier is sodium dodecyl sulfate, and the amount is 2% of the weight of butyl acrylate and methyl methacrylate, and the initiator is potassium persulfate, and the amount is 0.5% of the weight of butyl acrylate and methyl methacrylate;

[0089] Step A3, the third modification, introduction of fluorinated monomers:

[0090] In a reaction kettle equipped with a stirrer and a condenser, the second modified product B, perfluoroalkyl ethyl acrylate, emulsifier octylphenol polyoxyethylene ether and azobisisobutyronitrile are mixed with toluene as solvent, the reaction system is heated to 60° C., and reacted for 4 hours under nitrogen protection to obtain the third modified product C;

[0091] The mass ratio of the perfluoroalkyl ethyl acrylate to the second modified product B is 1:4, and the amount of the emulsifier octylphenol polyoxyethylene ether is 1% of the total mass of the second modified product B;

[0092] Step A4, fourth modification, cross-linking reaction:

[0093] The third modified product C was mixed with trimethylolpropane triacrylate and 1-hydroxy-cyclohexyl-phenyl-ketone, and a crosslinking reaction was carried out under ultraviolet light irradiation. The wavelength of ultraviolet light was 365nm and the irradiation intensity was 50mW / cm 2 , the irradiation time is 10 minutes to obtain a modified resin, and the final product modified resin is obtained;

[0094] The amount of trimethylolpropane triacrylate used is 2% of the mass of the third modified product C, and the amount of 1-hydroxy-cyclohexyl-phenyl-ketone used is 1% of the mass of trimethylolpropane triacrylate.

[0095] The preparation steps of the anti-corrosion coating are specifically as follows:

[0096] Step S1, polyurethane prepolymer synthesis:

[0097] In a reactor equipped with a stirrer, a thermometer and a nitrogen protection device, add polyether polyol and a catalyst into the reactor, heat it to 60°C, and stir evenly;

[0098] Slowly add diisocyanate dropwise, control the reaction temperature not to exceed 80°C, and continue the reaction at 70°C for 2 hours after the addition is completed to obtain a polyurethane prepolymer solution; a nitrogen atmosphere must be maintained during the reaction to prevent impurities such as moisture from interfering with the reaction.

[0099] Wherein, the diisocyanate is specifically toluene diisocyanate, and the amount of the diisocyanate is 80 parts by mass, which provides isocyanate groups for subsequent reactions; the polyether polyol is specifically polyoxypropylene glycol, and the amount of the polyoxypropylene glycol is 100 parts by mass, which serves as a soft segment to impart flexibility to the coating; the catalyst is specifically stannous octoate, and the amount thereof is 0.1 parts by mass, which is used to accelerate the reaction; the solvent is specifically ethyl acetate, which is used to adjust the viscosity of the system to facilitate the reaction;

[0100] Step S2, synthesis of silane coupling agent modified polyurethane prepolymer:

[0101] The polyurethane prepolymer solution obtained by the first reaction was cooled to 40°C, dibutyltin dilaurate was added, and stirred evenly, and then γ-glycidyloxypropyltrimethoxysilane was slowly added dropwise, and after the addition was completed, the mixture was reacted at 50°C for 3 hours;

[0102] The amount of γ-glycidyloxypropyltrimethoxysilane is 10 parts by mass, the silane coupling agent is used to enhance the adhesion between the coating and the outer wall of the pipe and introduce reactive groups, and the specific amount of dibutyltin dilaurate is 0.5 parts by mass, which serves as a catalyst for the reaction between the silane coupling agent and the polyurethane prepolymer;

[0103] The isocyanate groups in the polyurethane prepolymer react with the epoxy groups in KH-560, while the methoxy groups in the silane part can be involved in the subsequent hydrolysis reaction;

[0104] Step S3, introducing fluorinated acrylate monomer:

[0105] In a reactor, the product after the second reaction is mixed with an emulsifier and half of the initiator, and the temperature is raised to 70°C;

[0106] Slowly drop a mixture of perfluorooctyl ethyl acrylate and the remaining initiator, the drop time is controlled within 2 hours, the reaction temperature is maintained at 75° C., and after the reaction is completed, a fluorinated acrylate-modified polyurethane solution is obtained;

[0107] The fluorinated acrylate monomer undergoes polymerization reaction with the active groups (such as the remaining isocyanate groups or epoxy groups, etc.) on the polyurethane prepolymer under the action of the initiator;

[0108] The specific amount of perfluorooctyl ethyl acrylate is 10 parts by mass, the fluorine-containing monomer is used to improve the corrosion resistance and low surface energy characteristics of the coating, the initiator is specifically azobisisobutyronitrile, the amount of which is 0.5 parts by mass, used to initiate the polymerization reaction, and the emulsifier is specifically sodium dodecyl sulfate, the amount of which is 1 part by mass, which helps to disperse the monomer in the system;

[0109] Step S4, cross-linking reaction and toughening modification:

[0110] The product after the third reaction was mixed evenly with trimethylolpropane triacrylate, carboxylated nitrile rubber and 1-hydroxy-cyclohexyl-phenyl-ketone, and a cross-linking reaction was carried out under ultraviolet light irradiation. The ultraviolet light wavelength was 365 nm and the irradiation intensity was 50 mW / cm 2 The irradiation time is 10 minutes, and finally an anti-corrosion coating is obtained.

[0111] The third embodiment is based on the first and second embodiments:

[0112] A high rolling resistance MPVE double-wall corrugated pipe, comprising an inner layer, an intermediate reinforcement layer and an outer layer;

[0113] Wherein, the inner layer is specifically composed of the following components:

[0114] 70 parts by mass of MPVE alloy, 12 parts by mass of dioctyl phthalate, 4 parts by mass of calcium-zinc composite stabilizer, 1.5 parts by mass of antioxidant, 3 parts by mass of polyethylene wax, and 3 parts by mass of calcium stearate and zinc stearate composite lubricant;

[0115] The intermediate reinforcement layer is specifically composed of the following components:

[0116] 20 parts by mass of glass fiber, 15 parts by mass of glass microbeads, 60 parts by mass of MPVE alloy, 2 parts by mass of carbon nanotubes, 4 parts by mass of silane coupling agent, 10 parts by mass of dioctyl phthalate, 4 parts by mass of calcium zinc composite stabilizer, 1.5 parts by mass of calcium stearate and 1.5 parts by mass of antioxidant;

[0117] The outer layer is specifically composed of the following components:

[0118] 15 parts by mass of modified resin, 50 parts by mass of MPVE alloy, 1.5 parts by mass of phosphite antioxidant, 4 parts by mass of benzotriazole ultraviolet absorber, 5 parts by mass of masterbatch, 15 parts by mass of ceramic micropowder filler, 3 parts by mass of nano titanium dioxide filler, 8 parts by mass of plasticizer, 3 parts by mass of stabilizer, 1.5 parts by mass of corrosion inhibitor, and 7 parts by mass of anti-corrosion coating.

[0119] The preparation method of the modified resin is specifically as follows:

[0120] Step A1, first modification, maleic anhydride grafting:

[0121] The ethylene-vinyl acetate copolymer is preheated to 100° C. in a high-speed mixer, and then maleic anhydride and initiator dicumyl peroxide are added and mixed thoroughly, and the mixture is reacted and extruded in a twin-screw extruder to obtain a first modified product A;

[0122] The vinyl acetate content of the ethylene-vinyl acetate copolymer is 28%, the melt index is between 5g / 10min, the maleic anhydride accounts for 3% of the mass of the ethylene-vinyl acetate copolymer, and the initiator dicumyl peroxide accounts for 1% of the mass of the ethylene-vinyl acetate copolymer;

[0123] Step A2, second modification, copolymerization with acrylic ester monomers:

[0124] The first modified product A obtained was placed in a reactor, the reactor was heated to 80° C., an initiator and 50% of an emulsifier were added, and then butyl acrylate, methyl methacrylate and the remaining emulsifier were slowly added dropwise to obtain a second modified product B;

[0125] The mass ratio of butyl acrylate, methyl methacrylate and the first modified product A is 3:2:5, the emulsifier is sodium dodecyl sulfate, and the amount is 3% of the weight of butyl acrylate and methyl methacrylate, and the initiator is potassium persulfate, and the amount is 1% of the weight of butyl acrylate and methyl methacrylate;

[0126] Step A3, the third modification, introduction of fluorinated monomers:

[0127] In a reaction kettle equipped with a stirrer and a condenser, the second modified product B, perfluoroalkyl ethyl acrylate, emulsifier octylphenol polyoxyethylene ether and azobisisobutyronitrile are mixed with toluene as solvent, the reaction system is heated to 70° C., and reacted for 6 hours under nitrogen protection to obtain the third modified product C;

[0128] The mass ratio of the perfluoroalkyl ethyl acrylate to the second modified product B is 1:4, and the amount of the emulsifier octylphenol polyoxyethylene ether is 2% of the total mass of the second modified product B;

[0129] Step A4, fourth modification, cross-linking reaction:

[0130] The third modified product C was mixed with trimethylolpropane triacrylate and 1-hydroxy-cyclohexyl-phenyl-ketone, and a crosslinking reaction was carried out under ultraviolet light irradiation. The wavelength of ultraviolet light was 365nm and the irradiation intensity was 100mW / cm 2 , the irradiation time is 20 minutes to obtain a modified resin, and the final product modified resin is obtained;

[0131] The amount of trimethylolpropane triacrylate used is 3% of the mass of the third modified product C, and the amount of 1-hydroxy-cyclohexyl-phenyl-ketone used is 2% of the mass of trimethylolpropane triacrylate.

[0132] The preparation steps of the anti-corrosion coating are specifically as follows:

[0133] Step S1, polyurethane prepolymer synthesis:

[0134] In a reactor equipped with a stirrer, a thermometer and a nitrogen protection device, add polyether polyol and a catalyst into the reactor, heat it to 70°C, and stir evenly;

[0135] Slowly add diisocyanate dropwise, control the reaction temperature not to exceed 80°C, and continue the reaction at 80°C for 3 hours after the addition is completed to obtain a polyurethane prepolymer solution; a nitrogen atmosphere must be maintained during the reaction to prevent impurities such as moisture from interfering with the reaction.

[0136] Wherein, the diisocyanate is specifically toluene diisocyanate, and the amount of the diisocyanate is 100 parts by mass, which provides isocyanate groups for subsequent reactions; the polyether polyol is specifically polyoxypropylene glycol, and the amount of the polyoxypropylene glycol is 120 parts by mass, which serves as a soft segment to impart flexibility to the coating; the catalyst is specifically stannous octoate, and the amount thereof is 0.3 parts by mass, which is used to accelerate the reaction; the solvent is specifically ethyl acetate, which is used to adjust the viscosity of the system to facilitate the reaction;

[0137] Step S2, synthesis of silane coupling agent modified polyurethane prepolymer:

[0138] The polyurethane prepolymer solution obtained by the first reaction was cooled to 50°C, dibutyltin dilaurate was added, and stirred evenly, and then γ-glycidyloxypropyltrimethoxysilane was slowly added dropwise, and after the addition was completed, the mixture was reacted at 60°C for 4 hours;

[0139] The amount of γ-glycidyloxypropyltrimethoxysilane is 15 parts by mass, the silane coupling agent is used to enhance the adhesion between the coating and the outer wall of the pipe and introduce reactive groups, and the specific amount of dibutyltin dilaurate is 1 part by mass, which serves as a catalyst for the reaction between the silane coupling agent and the polyurethane prepolymer;

[0140] The isocyanate groups in the polyurethane prepolymer react with the epoxy groups in KH-560, while the methoxy groups in the silane part can be involved in the subsequent hydrolysis reaction;

[0141] Step S3, introducing fluorinated acrylate monomer:

[0142] In a reactor, the product after the second reaction is mixed with an emulsifier and half of the initiator, and the temperature is raised to 80°C;

[0143] Slowly drop a mixture of perfluorooctyl ethyl acrylate and the remaining initiator, the drop time is controlled within 3 hours, the reaction temperature is maintained at 85° C., and after the reaction is completed, a fluorinated acrylate-modified polyurethane solution is obtained;

[0144] The fluorinated acrylate monomer undergoes polymerization reaction with the active groups (such as the remaining isocyanate groups or epoxy groups, etc.) on the polyurethane prepolymer under the action of the initiator;

[0145] The specific amount of perfluorooctyl ethyl acrylate is 15 parts by mass, the fluorinated monomer is used to improve the corrosion resistance and low surface energy characteristics of the coating, the initiator is specifically azobisisobutyronitrile, the amount of which is 1 part by mass, used to initiate the polymerization reaction, and the emulsifier is specifically sodium dodecyl sulfate, the amount of which is 2 parts by mass, which helps to disperse the monomer in the system;

[0146] Step S4, cross-linking reaction and toughening modification:

[0147] The product after the third reaction was mixed evenly with trimethylolpropane triacrylate, carboxylated nitrile rubber and 1-hydroxy-cyclohexyl-phenyl-ketone, and a cross-linking reaction was carried out under ultraviolet light irradiation. The ultraviolet light wavelength was 365 nm and the irradiation intensity was 100 mW / cm 2 The irradiation time is 20 minutes, and finally an anti-corrosion coating is obtained.

[0148] The fourth embodiment is based on the first, second and third embodiments:

[0149] A high rolling resistance MPVE double-wall corrugated pipe, comprising an inner layer, an intermediate reinforcement layer and an outer layer;

[0150] Wherein, the inner layer is specifically composed of the following components:

[0151] 65 parts by mass of MPVE alloy, 9 parts by mass of dioctyl phthalate, 2 parts by mass of calcium-zinc composite stabilizer, 1 part by mass of antioxidant, 2 parts by mass of polyethylene wax, and 2 parts by mass of calcium stearate and zinc stearate composite lubricant;

[0152] The intermediate reinforcement layer is specifically composed of the following components:

[0153] 18 parts by mass of glass fiber, 12 parts by mass of glass microbeads, 55 parts by mass of MPVE alloy, 0.5 parts by mass of carbon nanotubes, 2 parts by mass of silane coupling agent, 6 parts by mass of dioctyl phthalate, 3.5 parts by mass of calcium zinc composite stabilizer, 1 part by mass of calcium stearate and 1 part by mass of antioxidant;

[0154] The outer layer is specifically composed of the following components:

[0155] 15 parts by mass of modified resin, 50 parts by mass of MPVE alloy, 1 part by mass of phosphite antioxidant, 3 parts by mass of benzotriazole ultraviolet absorber, 4 parts by mass of masterbatch, 12.5 parts by mass of ceramic micropowder filler, 2 parts by mass of nano titanium dioxide filler, 6 parts by mass of plasticizer, 2 parts by mass of stabilizer, 1 part by mass of corrosion inhibitor, and 7 parts by mass of anti-corrosion coating.

[0156] The preparation method of the modified resin is specifically as follows:

[0157] Step A1, first modification, maleic anhydride grafting:

[0158] The ethylene-vinyl acetate copolymer is preheated to 100° C. in a high-speed mixer, and then maleic anhydride and initiator dicumyl peroxide are added and mixed thoroughly, and the mixture is reacted and extruded in a twin-screw extruder to obtain a first modified product A;

[0159] The vinyl acetate content in the ethylene-vinyl acetate copolymer is 26%, the melt index is between 3.5g / 10min, the maleic anhydride accounts for 3% of the mass of the ethylene-vinyl acetate copolymer, and the initiator dicumyl peroxide accounts for 1% of the mass of the ethylene-vinyl acetate copolymer;

[0160] Step A2, second modification, copolymerization with acrylic ester monomers:

[0161] The first modified product A obtained was placed in a reactor, the reactor was heated to 80° C., an initiator and 50% of an emulsifier were added, and then butyl acrylate, methyl methacrylate and the remaining emulsifier were slowly added dropwise to obtain a second modified product B;

[0162] The mass ratio of butyl acrylate, methyl methacrylate and the first modified product A is 3:2:5, the emulsifier is sodium dodecyl sulfate, and the amount is 2% of the weight of butyl acrylate and methyl methacrylate, and the initiator is potassium persulfate, and the amount is 0.75% of the weight of butyl acrylate and methyl methacrylate;

[0163] Step A3, the third modification, introduction of fluorinated monomers:

[0164] In a reaction kettle equipped with a stirrer and a condenser, the second modified product B, perfluoroalkyl ethyl acrylate, emulsifier octylphenol polyoxyethylene ether and azobisisobutyronitrile are mixed with toluene as solvent, the reaction system is heated to 65° C., and reacted for 5 hours under nitrogen protection to obtain the third modified product C;

[0165] The mass ratio of the perfluoroalkyl ethyl acrylate to the second modified product B is 1:4, and the amount of the emulsifier octylphenol polyoxyethylene ether is 1.5% of the total mass of the second modified product B;

[0166] Step A4, fourth modification, cross-linking reaction:

[0167] The third modified product C was mixed with trimethylolpropane triacrylate and 1-hydroxy-cyclohexyl-phenyl-ketone, and a crosslinking reaction was carried out under ultraviolet light irradiation. The wavelength of ultraviolet light was 365nm and the irradiation intensity was 70mW / cm 2 , the irradiation time is 20 minutes to obtain a modified resin, and the final product modified resin is obtained;

[0168] The amount of trimethylolpropane triacrylate used is 2.5% of the mass of the third modified product C, and the amount of 1-hydroxy-cyclohexyl-phenyl-ketone used is 1.5% of the mass of trimethylolpropane triacrylate.

[0169] The preparation steps of the anti-corrosion coating are specifically as follows:

[0170] Step S1, polyurethane prepolymer synthesis:

[0171] In a reactor equipped with a stirrer, a thermometer and a nitrogen protection device, add polyether polyol and a catalyst into the reactor, heat it to 65°C, and stir evenly;

[0172] Slowly add diisocyanate dropwise, control the reaction temperature not to exceed 80°C, and continue the reaction at 75°C for 2.5 hours after the addition is completed to obtain a polyurethane prepolymer solution; a nitrogen atmosphere must be maintained during the reaction to prevent impurities such as moisture from interfering with the reaction.

[0173] Wherein, the diisocyanate is specifically toluene diisocyanate, and the amount of the diisocyanate is 90 parts by mass, which provides isocyanate groups for subsequent reactions; the polyether polyol is specifically polyoxypropylene glycol, and the amount of the polyoxypropylene glycol is 110 parts by mass, which serves as a soft segment to impart flexibility to the coating; the catalyst is specifically stannous octoate, and the amount thereof is 0.2 parts by mass, which is used to accelerate the reaction; the solvent is specifically ethyl acetate, which is used to adjust the viscosity of the system to facilitate the reaction;

[0174] Step S2, synthesis of silane coupling agent modified polyurethane prepolymer:

[0175] The polyurethane prepolymer solution obtained by the first reaction was cooled to 44°C, dibutyltin dilaurate was added, and stirred evenly, and then γ-glycidyloxypropyltrimethoxysilane was slowly added dropwise, and after the addition was completed, the mixture was reacted at 55°C for 3.5 hours;

[0176] The amount of γ-glycidyloxypropyltrimethoxysilane used is 12.5 parts by mass, the silane coupling agent is used to enhance the adhesion between the coating and the outer wall of the pipe and introduce reactive groups, and the specific amount of dibutyltin dilaurate used is 0.6 parts by mass, which serves as a catalyst for the reaction between the silane coupling agent and the polyurethane prepolymer;

[0177] The isocyanate groups in the polyurethane prepolymer react with the epoxy groups in KH-560, while the methoxy groups in the silane part can be involved in the subsequent hydrolysis reaction;

[0178] Step S3, introducing fluorinated acrylate monomer:

[0179] In a reactor, the product after the second reaction is mixed with an emulsifier and half of the initiator, and the temperature is raised to 75°C;

[0180] Slowly drop a mixture of perfluorooctyl ethyl acrylate and the remaining initiator, the drop time is controlled to be 2.5 hours, the reaction temperature is maintained at 80° C., and after the reaction is completed, a fluorinated acrylate-modified polyurethane solution is obtained;

[0181] The fluorinated acrylate monomer undergoes polymerization reaction with the active groups (such as the remaining isocyanate groups or epoxy groups, etc.) on the polyurethane prepolymer under the action of the initiator;

[0182] The specific amount of perfluorooctyl ethyl acrylate is 12.5 parts by mass, the fluorinated monomer is used to improve the corrosion resistance and low surface energy characteristics of the coating, the initiator is specifically azobisisobutyronitrile, the amount of which is 0.75 parts by mass, which is used to initiate the polymerization reaction, and the emulsifier is specifically sodium dodecyl sulfate, the amount of which is 1.5 parts by mass, which helps to disperse the monomer in the system;

[0183] Step S4, cross-linking reaction and toughening modification:

[0184] The product after the third reaction was mixed evenly with trimethylolpropane triacrylate, carboxylated nitrile rubber and 1-hydroxy-cyclohexyl-phenyl-ketone, and a cross-linking reaction was carried out under ultraviolet light irradiation. The ultraviolet light wavelength was 365nm and the irradiation intensity was 75mW / cm 2 The irradiation time is 15 minutes, and finally an anti-corrosion coating is obtained.

[0185] Comparative Example 1: Based on Example 4, the modified resin is removed, and the remaining components and preparation methods are the same as those of Example 4;

[0186] Comparative Example 2: Based on Example 4, the anti-corrosion coating is removed, and the remaining components and preparation methods are the same as those of Example 4.

[0187] Performance testing;

[0188] 1. Test samples;

[0189] Examples 2, 3 and 4 samples: MPVE double-wall corrugated pipes with high rolling resistance made according to the complete formulas of Examples 2, 3 and 4;

[0190] Comparative Example 1 Sample: MPVE double-wall corrugated pipe with the modified resin removed and the remaining components and preparation method being the same as those in Example 4, used for comparative analysis of the contribution of the modified resin to the pipe performance;

[0191] Comparative Example 2 Sample: The MPVE double-wall corrugated pipe with the anti-corrosion coating removed and the remaining components and preparation methods being the same as those in Example 4, aims to explore the role of the anti-corrosion coating in the comprehensive performance of the pipe.

[0192] 2. Test methods;

[0193] (1) High rolling resistance test:

[0194] Using a pipe rolling tester, place the sample horizontally on the tester platform, set different levels of pressure, load the pressure at a constant rate, maintain each pressure level for a certain time, observe the deformation and rupture of the pipe appearance, and record the maximum pressure value that can be tolerated without damage.

[0195] (2) Corrosion resistance test:

[0196] The pipe samples were immersed in hydrochloric acid and sodium hydroxide solutions of different concentrations, placed in a constant temperature and humidity chamber, taken out regularly to observe the corrosion of the pipe surface, and the mass change of the samples before and after corrosion was measured by weighing method to calculate the corrosion rate.

[0197] (3) Physical and mechanical properties test:

[0198] According to the plastic tensile properties test standard, a universal material testing machine is used to stretch the dumbbell-shaped pipe specimen at a specified tensile rate until it breaks, and the maximum tensile force at break is recorded to calculate the tensile strength.

[0199] 3. Test results

[0200]

[0201]

[0202] 3. Conclusion

[0203] (1) The MPVE double-wall corrugated pipes with high rolling resistance of Examples 2, 3 and 4 have excellent performance in high rolling resistance, corrosion resistance, physical and mechanical properties, etc. due to their complete formula and reasonable preparation process. All indicators meet the requirements of the corresponding standards. The materials of each layer and the key components (modified resin, anti-corrosion coating) cooperate with each other to meet the requirements of the harsh use environment.

[0204] (2) Modified resin is of great significance to improving the rolling resistance, corrosion resistance and physical and mechanical properties of pipes. Multiple modifications are used to optimize the structure and performance, strengthen the matrix and improve the interface bonding, which is one of the key factors to ensure the overall quality of pipes.

[0205] (3) The anti-corrosion coating effectively blocks the erosion of external corrosive media, and at the same time plays an important role in assisting anti-rollover and maintaining the integrity of physical and mechanical properties. Both are indispensable and lay the foundation for the long-term and stable service of the product. The product in Example 2 has no anti-corrosion coating, so its corrosion resistance and overall performance have declined significantly, deviating from the standard requirements.

[0206] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.

Claims

1. A MPVE double-wall corrugated pipe with high rolling resistance, characterized in that: It includes an inner layer, a middle reinforcement layer and an outer layer; Wherein, the inner layer is specifically composed of the following components: 60-70 parts by mass of MPVE alloy, 8-12 parts by mass of dioctyl phthalate, 2-4 parts by mass of calcium-zinc composite stabilizer, 0.5-1.5 parts by mass of antioxidant, 1-3 parts by mass of polyethylene wax, and 1-3 parts by mass of calcium stearate and zinc stearate composite lubricant; The intermediate reinforcement layer is specifically composed of the following components: 15-20 parts by mass of glass fiber, 10-15 parts by mass of glass microbeads, 50-60 parts by mass of MPVE alloy, 0.5-2 parts by mass of carbon nanotubes, 2-4 parts by mass of silane coupling agent, 6-10 parts by mass of dioctyl phthalate, 2-4 parts by mass of calcium zinc composite stabilizer, 0.5-1.5 parts by mass of calcium stearate and 0.5-1.5 parts by mass of antioxidant; The outer layer is specifically composed of the following components: 10-15 parts by mass of modified resin, 40-50 parts by mass of MPVE alloy, 0.5-1.5 parts by mass of phosphite antioxidant, 2-4 parts by mass of benzotriazole ultraviolet absorber, 3-5 parts by mass of masterbatch, 10-15 parts by mass of ceramic micropowder filler, 1-3 parts by mass of nano titanium dioxide filler, 5-8 parts by mass of plasticizer, 1-3 parts by mass of stabilizer, 0.5-1.5 parts by mass of corrosion inhibitor and 3-7 parts by mass of anti-corrosion coating.

2. The MPVE double-wall corrugated pipe with high rolling resistance according to claim 1, characterized in that: The preparation method of the modified resin is specifically as follows: Step A1, first modification: Preheating ethylene-vinyl acetate copolymer to 80-100° C. in a high-speed mixer, then adding maleic anhydride and initiator dicumyl peroxide, mixing thoroughly, and reacting and extruding the mixture in a twin-screw extruder to obtain a first modified product A; Step A2, second modification: The first modified product A obtained is placed in a reactor, the reactor is heated to 70-80° C., an initiator and 30%-50% of an emulsifier are added, and then butyl acrylate, methyl methacrylate and the remaining emulsifier are slowly added dropwise to obtain a second modified product B; Step A3, third modification: In a reaction kettle, using toluene as solvent, the second modified product B, perfluoroalkyl ethyl acrylate, emulsifier octylphenol polyoxyethylene ether and azobisisobutyronitrile are mixed to obtain the third modified product C; Step A4, fourth modification: The third modified product C is mixed with trimethylolpropane triacrylate and 1-hydroxy-cyclohexyl-phenyl-ketone to obtain the final product modified resin.

3. The MPVE double-wall corrugated pipe with high rolling resistance according to claim 1, characterized in that: The preparation steps of the anti-corrosion coating are specifically as follows: Step S1, polyurethane prepolymer synthesis: In a reaction kettle, polyether polyol and a catalyst are added to the reaction kettle, stirred evenly, and diisocyanate is slowly added dropwise to obtain a polyurethane prepolymer solution; Step S2, synthesis of silane coupling agent modified polyurethane prepolymer: The polyurethane prepolymer solution obtained by the first reaction is cooled to 40-50°C, dibutyltin dilaurate is added, stirred evenly, and then γ-glycidyloxypropyltrimethoxysilane is slowly added dropwise. After the addition is completed, the mixture is reacted at 50-60°C for 3-4 hours; Step S3, introducing fluorinated acrylate monomer: In a reactor, mix the product after the second reaction with an emulsifier and half of the initiator, and heat to 70-80°C; Slowly adding a mixture of perfluorooctyl ethyl acrylate and the remaining initiator dropwise, and obtaining a fluorinated acrylate-modified polyurethane solution after the reaction is completed; Step S4, cross-linking reaction and toughening modification: The product after the third reaction is mixed evenly with trimethylolpropane triacrylate, carboxyl nitrile rubber and 1-hydroxy-cyclohexyl-phenyl-ketone, and cross-linked under ultraviolet light to finally obtain an anti-corrosion coating.

4. The MPVE double-wall corrugated pipe with high rolling resistance according to claim 3 is characterized in that: In the step S1, the temperature of the time-space reaction of the diisocyanate addition is not more than 80° C., and the reaction is continued at 70-80° C. for 2-3 hours after the addition is completed.

5. The MPVE double-wall corrugated pipe with high rolling resistance according to claim 4, characterized in that: In step S3, the dropping time is controlled at 2-3 hours, and the reaction temperature is maintained at 75-85°C.

6. The MPVE double-wall corrugated pipe with high rolling resistance according to claim 5, characterized in that: In step S4, the wavelength of ultraviolet light is 365nm, and the irradiation intensity is 50-100mW / cm 2 The irradiation time is 10-20 minutes.

7. The method for preparing a MPVE double-wall corrugated pipe with high rolling resistance according to claim 1, characterized in that: The steps include: Step D1, according to the inner layer formula, accurately weigh the MPVE alloy, dioctyl phthalate, calcium zinc composite stabilizer, antioxidant, polyethylene wax and calcium stearate and zinc stearate composite lubricant, and place them in containers for standby use; The weighed MPVE alloy is put into a high-speed mixer, and dioctyl phthalate, calcium zinc composite stabilizer, antioxidant, polyethylene wax, and calcium stearate and zinc stearate composite lubricant are added in sequence during stirring. The stirring is continued during the feeding process, and the mixing time is controlled within 10-15 minutes to obtain a preliminarily mixed and uniform inner layer material; The inner layer material after high-speed mixing is transported to the twin-screw extruder, and the die head extrude to form the inner layer tube blank; Step D2, drying the glass fibers and glass microbeads, weighing the carbon nanotubes and the silane coupling agent, and stirring to obtain modified carbon nanotubes; Weighing the treated glass fibers, glass microbeads, modified carbon nanotubes, MPVE alloy, dioctyl phthalate, calcium zinc composite stabilizer, calcium stearate and antioxidant, putting them into a high-speed mixer, and extruding them through an extruder to obtain a middle layer material; Step D3, accurately weighing materials according to the outer layer formula, pre-dispersing the ceramic micropowder filler and the nano titanium dioxide filler, adding the weighed raw materials into a mixer, first adding the MPVE alloy and the modified resin and starting stirring, then adding the phosphite antioxidant, the benzotriazole ultraviolet absorber, the masterbatch, the dispersed ceramic micropowder filler, the nano titanium dioxide filler, the plasticizer, the stabilizer, the corrosion inhibitor and the anti-corrosion coating, mixing and extruding through an extruder to obtain the outer layer material; Step D4: using a mold, the inner layer tube blank, the middle layer material, and the outer layer material are extruded simultaneously, and the extruded three-layer integrated tube blank is placed in a vacuum setting machine to finally produce a double-wall corrugated pipe finished product.

8. The MPVE double-wall corrugated pipe with high rolling resistance and the preparation method thereof according to claim 7, characterized in that: In the step D2, the carbon nanotubes and the silane coupling agent are weighed and put into a stirrer and stirred for 30-60 minutes.

9. The MPVE double-wall corrugated pipe with high rolling resistance and its preparation method according to claim 7, characterized in that: The die used in step D4 is specifically a co-extrusion die, and the overall extrusion speed is 1-2 m / min.

10. The MPVE double-wall corrugated pipe with high rolling resistance and its preparation method according to claim 7, characterized in that: The vacuum degree of the vacuum setting machine in step D4 is -0.08 to -0.1 MPa, and cooling is performed by a circulating water cooling system, and the cooling water temperature is controlled at 15-25°C.